Children's Liability in Traffic Criminal Actions (Case Study Decision Number: 273 / Pid.Sus / 2019 / PN Gsk) - Devan Lismatika Nugraha (Faculty of Law Universitas Muhammadiyah Purwokerto, 2021)
This study aims to analyze the court decision number: 273 / Pid.Sus / 2019 / PN Gsk. The method used is normative legal research. The data used is secondary data, including books, scientific journals, research results, and laws and regulations. The data obtained were then analyzed normatively qualitatively. The results of this verdict indicate that first, the defendant M Nastain Bin Kariyanto was proven legally and proven to have committed a criminal act of